Study on Health and Socioeconomic Status of Mothers and Children Living in Bijeswari Army Family Quarter - Shrestha, Khagendra Bahadur; Thapa, Narbada (Medical Journal of Shree Birendra Hospital, 2000)
Study on Health and Socioeconomic Status of Mothers and Children Living in Bijeswari Army Family Quarter